Introduction to homeland security - Bullock, Jane A. (Amsterdam ; Boston : Butterworth-Heinemann, 2006)
Completely revised and updated new edition of best-selling text complete with full color throughout!
Historic overview of the terrorist threat -- Statutory authority -- Organizational actions -- Terrorist-related hazards -- Safety and security -- Mitigation, prevention, and preparedness -- Response and recovery -- Communications -- Technology -- The future of homeland security.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Terrorism -- Prevention -- Government policy -- United States; National security -- United States; Civil defense -- United States; Emergency management -- United States; Terrorisme -- Prévention -- Politique gouvernementale -- États-Unis.; POLITICAL SCIENCE -- Political Freedom & Security -- Law Enforcement; Civil defense; Emergency management; National security; Terrorism -- Prevention -- Government policy; United States; dissertations; Academic theses; Academic theses; Thèses et écrits académiques.